2020
DOI: 10.1017/jfm.2019.1063
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity of the turbulent precessing vortex core: synchronization experiments and global adjoint linear stability analysis

Abstract: The Precessing Vortex Core (PVC) is a coherent structure that can arise in swirling jets from a global instability. In this work, the PVC is investigated under highly turbulent conditions. The goal is to characterize the receptivity of the PVC to active flow control, both theoretically and experimentally. Based on stereoscopic particle image velocimetry and surface pressure measurements, the experimental studies are facilitated by Fourier decomposition and proper orthogonal decomposition. The frequency and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…(2015) and Müller et al. (2020).
Figure 2.Schematic of the experimental set-up and the utilised measurement systems: HS PIV, high-speed particle image velocimetry; AMP, amplifier; DAQ, data acquisition system.
…”
Section: Experimental Details and Observations Of Swirling Jet Dynamicsmentioning
confidence: 95%
See 3 more Smart Citations
“…(2015) and Müller et al. (2020).
Figure 2.Schematic of the experimental set-up and the utilised measurement systems: HS PIV, high-speed particle image velocimetry; AMP, amplifier; DAQ, data acquisition system.
…”
Section: Experimental Details and Observations Of Swirling Jet Dynamicsmentioning
confidence: 95%
“…In these cases, the failure of the mean-flow model is related to a strong nonlinear interaction between the fundamental mode and the first harmonic. The present investigation covers the global mode in a swirling jet, for which it was shown that the saturation is governed by the mean-flow change (Müller et al 2020).…”
Section: Linear Instabilities In Turbulent Flowsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the greatest benefits of the LSA framework lies in its adjoint formulation. The adjoint LSA allows, amongst others, for identifying regions of receptivity to periodic forcing [3,4,5] and sensitivity to mean flow modifications [6,7,8]. Previous works have already discussed the PVC in the light of the LSA [9,10].…”
Section: Introductionmentioning
confidence: 99%